Zero Cost Policy for Indonesian Migrant Workers in Taiwan Case Study Based Employment Agreement Law Number 18 of 2017 - Taria Hasna Setyawulandari; Satino, Satino (Journal of Law, Politic and Humanities, 2024)
Indonesian migrant workers often encounter the issue of placement expenses. To address this issue, the Indonesian government has implemented Law Number 18 of 2017, which aims to protect Indonesian migrant workers. According to Article 30, paragraph (1), Indonesian Migrant Workers are exempt from paying placement fees. The government's primary priority is to safeguard and ensure the rights and duties of migrant workers via the policy of waiving placement fees, often known as zero cost. The employment agreement does not include a specific provision for the zero cost policy, resulting in migrant workers still being required to pay placement fees. This study used a normative juridical research methodology to examine the hierarchical structure of relevant laws, regulations, and legal principles in work agreement.